The Importance of Intraoperative Cholangiography during Laparoscopic Cholecystectomy - Polat, Fatin R. (Society of Laparoendoscopic Surgeons, 2000)
Laparoscopic cholecystectomy (LC) using an electrosurgery energy source was successfully performed in 59 (95%) out of 62 selected patients. The procedures were performed by different surgical teams at Trakya University, Medical Fakulty, in the department of General Surgery and the Karl-Franzens-University School of Medicine, in the department of General Surgery. Cholangiography was routine at Karl Franzens University and selective at Trakya University. Laparoscopic intraoperative cholangiography (IOC) was performed in 48 (81.3%) patients, and open IOC was performed in 3 patients. Two patients had common duct stones; one of which was unsuspected preoperatively. These cases underwent endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic papillotomy (EP). One patient had a choledocal tumor, unsuspected preoperatively. Anatomical anomalies were not identified. Cholangiography could not be performed in one case in which there was no suspected pathology. ERCP was performed on one patient 30 days after being discharged because of acute cholangitis. In this case, residual stones were identified in the choledocus. Four patients underwent open cholecystectomy because of tumor, unidentified cystic duct or common bile duct pathology that could not be visualized on the cholangiogram. Our study suggests that cholangiography performed via the cystic duct before any structures are divided can prevent the most serious complication of laparoscopic cholecystectomy – common duct injury. We recommend that cholangiography be attempted on all patients undergoing LC.